A Survey on flow meters based on application - S R, Sakthivel; K, Sudarshan; Venkateswaran V, Balaji (International Journal of Engineering and Technology, 2018)
Flow meters are those instruments that are used to measure the flow of fluid. The term fluid is a quite general because it involves both liquids and gases, so technically flow meters are those instruments that are used to measure the flow of liquids and gases. There have been numerous classifications for fluids, based on viscosity, operating pressure and temperature and even based on the type of measurement, whether it is done in a conduit or out in the open. The main objective of this paper is to develop a reference table based on the various applications of flow meters.